Knowledge, attitudes and factors associated with acceptability of human papillomavirus vaccination among undergraduate medical, dental and nursing students in South India - Seemitha Shetty; Sumathi Prabhu; Veena Shetty; Avinash K. Shetty (Taylor & Francis Group, 2019)
Purpose: To evaluate knowledge, attitudes and factors associated with acceptability of human papillomavirus (HPV) vaccine among undergraduate medical, dental, and nursing students in South India. Methods: Using a post-test study design, a convenience sample of 988 students (age 18-26 years) were surveyed. The primary outcome was vaccine acceptability (likely to intend to receive the vaccine). Bivariate analysis using Chi-Square test of independence and multivariate binary logistic regression analysis was used to examine factors associated with vaccine acceptability. Results: Out of 988 students surveyed, majority had heard about cervical cancer (95%), HPV (89.3) or genital warts(77.5). Only 59.7% had heard of HPV vaccine prior to the survey; 65.2% intended to receive the vaccine and 68.3% were willing to recommend the vaccine to others. Participants aged <22 years were less likely to accept the vaccine (OR:0.85, CI:0.76-0.96) compared with participants aged older than 22 years. Medical students (OR:1.12, CI:1.03-1.23), students who reported alcohol use (OR:1.15, CI:1.03-1.29) and those with moderate knowledge scores were more likely to intend to receive the vaccine (OR:1.14, CI:1.04-1.24), compared to others. On multivariate analysis, only course (OR 1.366, CI 1.016-1.835) and attitude score (OR 4.17; CI 2.12-8.2) were statistically associated with intention to receive the HPV vaccine. Conclusion: Two-thirds of students intended to receive the HPV vaccine. Although the overall awareness of the HPV-related disease and prevention is good, considerable knowledge gaps exists in many areas suggesting that that more education about HPV disease and benefits of vaccination should be included in the undergraduate medical school curriculum.